2015
DOI: 10.1590/s1806-37132015000000077
|View full text |Cite
|
Sign up to set email alerts
|

The rapid shallow breathing index as a predictor of successful mechanical ventilation weaning: clinical utility when calculated from ventilator data

Abstract: OBJECTIVE: The use of the rapid shallow breathing index (RSBI) is recommended in ICUs, where it is used as a predictor of mechanical ventilation (MV) weaning success. The aim of this study was to compare the performance of the RSBI calculated by the traditional method (described in 1991) with that of the RSBI calculated directly from MV parameters. METHODS: This was a prospective observational study involving patients who had been on MV for more than 24 h and were candidates for weaning. The RSBI was obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
1
13
0
3
Order By: Relevance
“…This similar study revealed no association between the RSBI measurements and extubation outcomes [ 20 ]. In other studies about pediatric patients in general, they found an association between the measurements of RSBI prior to extubation and the extubation outcomes which is a prediction of extubation success with low RSBI similar to the results in the two hours prior to extubation RSBI measurements in our study [ 9 , 10 , 22 , 23 ]. Unlike our study, some of these studies established a threshold, cut-off point, to predict the successful extubation, but these cut-off points were variable and ranging from 6.7 to 11 [ 9 , 10 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This similar study revealed no association between the RSBI measurements and extubation outcomes [ 20 ]. In other studies about pediatric patients in general, they found an association between the measurements of RSBI prior to extubation and the extubation outcomes which is a prediction of extubation success with low RSBI similar to the results in the two hours prior to extubation RSBI measurements in our study [ 9 , 10 , 22 , 23 ]. Unlike our study, some of these studies established a threshold, cut-off point, to predict the successful extubation, but these cut-off points were variable and ranging from 6.7 to 11 [ 9 , 10 , 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…For pediatric group, same equation for RSBI is used with a correction by weight, and it is usually calculated during a two-hour spontaneous breathing trial (SBT) [ 9 ]. Multiple studies considered RSBI lower than 105 breath/min/L as a predictor for successful extubation in adult group [ 10 - 12 ]. Although RSBI threshold has been calculated and defined for adults, the threshold among pediatric patients still unclear yet [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One interesting finding presented by Souza et al 1 is that even if there is significant difference in the direct comparison of the RSBI obtained by spirometry or directly from the ventilator, the two are very similar in terms of accuracy, which justifies the use of either method. Although we observed a statistically significant difference in the direct comparison of measurement methods, the values obtained in both groups were below 105, which is indicative of successful weaning.…”
mentioning
confidence: 95%
“…First, we would like to congratulate Souza et al for their article entitled "The rapid shallow breathing index as a predictor of successful mechanical ventilation weaning: clinical utility when calculated from ventilator data", recently published in the JBP. 1 The subject is of great importance for professionals in the intensive care unit, and the article presents a new tool for the evaluation of critically ill patients on mechanical ventilation.…”
mentioning
confidence: 99%
See 1 more Smart Citation